Walnut oil prevents hyperlipidemia induced by high-fat diet and regulates intestinal flora and liver metabolism - Yang, Rui; Chen, Dan; Chen, Yanling; Ma, Yage; Chen, Chaoyin; Zhao, Shenglan (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to investigate the preventive effect of walnut oil as medicinal food on abnormal lipid metabolism and its influence on liver metabolites and intestinal flora.MethodsThe rat model of abnormal lipid metabolism was established by feeding high-fat diet and administering a high-fat emulsion via gavage. The rats were randomly assigned to one of the five groups: the normal group (ND), the model group (HFD), and three walnut oil intervention groups differing in dosage [low-dose (OL, 2.5 g/kg. BW/day), medium-dose (OM, 5 g/kg. BW/day) and high-dose (OH, 10 g/kg. BW/day)]. Modeling and administration were performed simultaneously for 10 weeks. After the last administration, the serum and organs of the animals were collected under anesthesia, and the organ index was analyzed. Serum total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C) were measured. A histopathological examination of the liver was performed, and the intestinal flora was detected by Illumina technology.ResultsCompared to the ND group, the HFD group exhibited a significant increase in body weight and Lee’s index. Compared to the HFD group, each walnut oil intervention group showed a relatively reduced degree of liver swelling and a significant decrease in fat vacuoles within the cytoplasm. Levels of TC, TG, LDL-C, activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly decreased (p < 0.05), while HDL-C levels were increased (p < 0.05), along with a significant increase in the activity of glutathione peroxidase (GSH-PX) and a decrease in malondialdehyde (MDA) content in serum. These findings indicated that walnut oil could improve the blood lipid profile in hyperlipidemia-model rats. The results of intestinal flora showed that at the genus level, there were significant increases in the relative abundance of Collinsella and Blautia (p < 0.01) while significant decreases of Oscillospira and Allobaculum (p < 0.01) in the HFD group vs. the ND group. However, these flora changes were impeded although only Collinslla (p < 0.05) in the OL group. Metabonomics analysis identified that a total of 19 potential biomarkers were screened out from the differential metabolites with |log2FC| > 1, VIP > 1 and p < 0.05.ConclusionWalnut oil can significantly prevent hyperlipidemia caused by high-fat diet. The mechanism is mainly through significantly reducing the content of MDA and the activities of ALT and AST, significantly increasing the activity of GSH-PX, and improving intestinal flora and liver metabolism.